2020
DOI: 10.1177/0143624420911810
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on tracer gas method for building infiltration rate measurement

Abstract: The use of occupant-exhaled CO2 as the tracer gas enables the actual indoor infiltration rate to be measured, but the number and location of measuring points have a great impact on the accuracy of the results. This paper compares the experimental results from two tracer gas measurement techniques, decay with SF6 and constant injection with CO2 (exhaled by occupant). The results show a deviation of –9.0 to 7.4% between these two methods. This paper compares the result of this study with previous ones, and it co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The uncertainty of the design infiltration rate can also be estimated. Possible approaches involve the use of tracer gases tests [ 67 ], CFD-assisted air-velocity method [ 68 ] and Bayesian calibration [ 69 ]. For quantifying the infectious risk in anti-infection mode, we selected the scenario in which the masks and filters were not used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uncertainty of the design infiltration rate can also be estimated. Possible approaches involve the use of tracer gases tests [ 67 ], CFD-assisted air-velocity method [ 68 ] and Bayesian calibration [ 69 ]. For quantifying the infectious risk in anti-infection mode, we selected the scenario in which the masks and filters were not used.…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainty of the design infiltration rate can also be estimated. Possible approaches involve the use of tracer gases tests [ 67 ], CFD-assisted air-velocity method [ 68 ] and Bayesian calibration [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The air change rates estimated with SF6 and CO2 were in good agreement. Men, Wang and Zou [25] compared the air change rates estimated through SF6-based tracer gas decay tests to CO2based tracer gas constant injection tests and concluded that the difference between the results was, in general, less than 10%. SF6 and CO2 are both widely used tracer gases.…”
Section: Introductionmentioning
confidence: 99%